Topic salience and political polarization: Evidence from the German "PISA shock" - Pietro Sancassani (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Does the salience of a topic affect polarization in related parliamentary debates? When discussing a salient topic, politicians might adopt more extreme stances to gain electoral consensus. Alternatively, they could converge towards more moderate positions to find a compromise. Using parliamentary debates from the 16 German state parliaments, I exploit the exogenous increase in the salience of education induced by the unexpectedly low performance of German students in the PISA 2000 test-the German "PISA shock". I combine machine-learning and text analysis techniques to obtain topic-specific measures of polarization of parliamentary debates. In a difference-in-differences framework, I find that the PISA shock caused an 8.8% of a standard deviation increase in polarization of education debates compared to other topics. The effect is long-lasting and fades after about six years.
Keywords: D72; D71; 330; polarization; text analysis; machine learning; Germany; PISA shock